Inoculation With Indigenous Rhizosphere Microbes Enhances Aboveground Accumulation of Lead in Salix integra Thunb. by Improving Transport Coefficients - Niu, Xiao-yun; Wang, Shao-kun; Zhou, Jian; Di, Dong-liu; Sun, Pai; Huang, Da-zhuang (Frontiers in Microbiology, 2021)
The application of plant–microbial remediation of heavy metals is restricted by the difficulty of exogenous microbes to form large populations and maintain their long-term remediation efficiency. We therefore investigated the effects of inoculation with indigenous heavy-metal-tolerant rhizosphere microbes on phytoremediation of lead (Pb) by Salix integra. We measured plant physiological indexes and soil Pb bioavailability and conducted widespread targeted metabolome analysis of strains to better understand the mechanisms of enhance Pb accumulation. Growth of Salix integra was improved by both single and co-inoculation treatments with Bacillus sp. and Aspergillus niger, increasing by 14% in co-inoculated plants. Transfer coefficients for Pb, indicating mobility from soil via roots into branches or leaves, were higher following microbial inoculation, showing a more than 100% increase in the co-inoculation treatment over untreated plants. However, Pb accumulation was only enhanced by single inoculation treatments with either Bacillus sp. or Aspergillus niger, being 10% greater in plants inoculated with Bacillus sp. compared with uninoculated controls. Inoculation mainly promoted accumulation of Pb in aboveground plant parts. Superoxide dismutase and catalase enzyme activities as well as the proline content of inoculated plants were enhanced by most treatments. However, soil urease and catalase activities were lower in inoculated plants than controls. Proportions of acid-soluble Pb were 0.34% and 0.41% higher in rhizosphere and bulk soil, respectively, of plants inoculated with Bacillus sp. than in that of uninoculated plants. We identified 410 metabolites from the microbial inoculations, of which more than 50% contributed to heavy metal bioavailability; organic acids, amino acids, and carbohydrates formed the three major metabolite categories.These results suggest that both indigenous Bacillus sp. and Aspergillus niger could be used to assist phytoremediation by enhancing antioxidant defenses of Salix integra and altering Pb bioavailability. We speculate that microbial strains colonized the soil and plants at the same time, with variations in their metabolite profiles reflecting different living conditions. We also need to consider interactions between inocula and the whole microbial community when applying microbial inoculation to promote phytoremediation.